2019
DOI: 10.17509/ijal.v9i1.15933
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between pronunciation self-efficacy sources and self-efficacy beliefs: A structural equation modeling approach

Abstract: This study was conducted to find the association between pronunciation self-efficacy sources and pronunciation self-efficacy beliefs. It was quantitative in nature using a correlational research design. A sample of 155 Malaysian ESL university students was selected from two Malaysian universities by employing proportionate stratified random sampling. Two questionnaires were used to collect the data related to pronunciation self-efficacy sources and self-efficacy beliefs. In order to analyze the collected data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…Thus, the current study's findings could be attributed to the possibility that Saudi EFL students might have experienced positive mastery experience related to reading, which were responsible for increasing their reading selfefficacy beliefs. This finding is consistent with a number of studies (Arslan, 2012;Chen & Usher, 2013;Kaya & Bozdag, 2016;Kiran & Sungur, 2012;Kudo & Mori, 2015;Lin, 2016;Lin & Tsai, 2018;Phan, 2012;Phan & Ngu, 2016;Shehzad, Alghorbany, Lashari, Lashari, & Razzaq, 2019;Usher & Pajares, 2009). The aforementioned speculation requires further approval from future studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, the current study's findings could be attributed to the possibility that Saudi EFL students might have experienced positive mastery experience related to reading, which were responsible for increasing their reading selfefficacy beliefs. This finding is consistent with a number of studies (Arslan, 2012;Chen & Usher, 2013;Kaya & Bozdag, 2016;Kiran & Sungur, 2012;Kudo & Mori, 2015;Lin, 2016;Lin & Tsai, 2018;Phan, 2012;Phan & Ngu, 2016;Shehzad, Alghorbany, Lashari, Lashari, & Razzaq, 2019;Usher & Pajares, 2009). The aforementioned speculation requires further approval from future studies.…”
Section: Discussionsupporting
confidence: 90%
“…In other words, the findings indicated that whenever Saudi EFL learners observed their peers or other models performing well in reading, their reading self-efficacy beliefs increased. This finding is supported by several other studies (Britner & Pajares, 2006;Chen & Usher, 2013;Kaya & Bozdag, 2016;Lin, 2016;Lin & Tsai, 2018;Phan & Ngu, 2016;Shehzad et al, 2019;Tschannen--Moran & McMaster, 2009). 'Social cognitive theory' also affirmed that one can observe other successful peers/role models and their success can persuade one to believe that one can accomplish similar task (Bandura, 1986).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, various studies have been conducted in a university setting (Oh, 2016;Shang, 2010;Shehzad et al, 2019;Tabrizi & Jafari, 2015;Yoğurtçu, 2013), and have revealed a significant connection between self-efficacy and reading comprehension, with the exception of Yoğurtçu's (2013) study. Yoğurtçu (2013) discovered that reading comprehension self-efficacy was associated with reading comprehension skills for high self-efficacious students.…”
Section: Self-efficacy Beliefs and Reading Comprehensionmentioning
confidence: 99%
“…In fact, just one (quantitative) research study investigating the relationship between self-efficacy sources and reading comprehension (i.e. Shehzad et al, 2019) was found when preparing this article. In order to gain a more robust insight into the aforementioned variables, it is vital to conduct research using a qualitative approach.…”
Section: Introductionmentioning
confidence: 99%